A beautiful day in the neighborhood [videorecording (DVD)] - Heller, Marielle; Hanks, Tom; Rhys, Matthew, 1974-; Cooper, Chris, 1951- (Sony Pictures Home Entertainment, 2020)
Tells the story of the friendship between the host of television series "Mister Rogers' neighborhood" Fred Rogers and journalist Tom Junod.